SIMULATION OF INSURANCE RISKS IN AGRICULTURE - Moiseev, Alexei; Jurevič, Kindaev Aleksandr (Journal of Applied Engineering Science, 2015)
Insurance is a powerful instrument of smoothing the losses resulting from economic activity. The key element of insurance process consideration is identification of insurance risks at various approaches to the formation of the insurance premium. Naturally, a more acceptable approach is identification of risks on the basis of insurance models, with the subsequent correction of results. This article is devoted to the problems of imitating modeling the insurance risks of losses in agriculture. Special attention is paid to the risks arising from the cultivation of the grain crops. Modeling is based on the model of individual risk with the assumption of the full coverage of the insurance field. Unlike classical approaches, the present article takes into account correlation of losses under separate contracts. When modeling, losses were supposed to submit to the normal law of distribution. The algorithm of generation of the random values correlated among them has been developed for the control of losses correlation. This algorithm is the cornerstone of the received results of risk of insurance. In this paper the analysis of distinctions in the results of insurance risks modeling at the account of losses correlation is carried out with the assumption of independence of the results of separate contracts. The account of losses correlation under contracts of insurance in agriculture allows a more precise approach to the determination of insurance premiums and to the development of regulation strategies of this type of insurance from the state for avoiding the fatal losses of insurance companies. Background: Insurance is a powerful instrument of smoothing the losses resulting from economic activity. The key element of insurance process consideration is identification of insurance risks at various approaches to the formation of the insurance premium. Naturally, a more acceptable approach is identification of risks on the basis of insurance models, with the subsequent correction of results. This article is devoted to the problems of imitating modeling the insurance risks of losses in agriculture. Special attention is paid to the risks arising from the cultivation of the grain crops. Methods: Modeling is based on the model of individual risk with the assumption of the full coverage of the insurance field. Unlike classical approaches, the present article takes into account correlation of losses under separate contracts. When modeling losses were supposed to submit to the normal law of distribution. Results: The algorithm of generation of the random values correlated among them has been developed for the control of losses correlation. This algorithm is the cornerstone of the received results of risk of insurance. In this paper the analysis of distinctions in the results of insurance risks modeling at the account of losses correlation is carried out with the assumption of independence of the results of separate contracts. Conclusions: The account of losses correlation under contracts of insurance in agriculture allows a more precise approach to the determination of insurance premiums and to the development of regulation strategies of this type of insurance from the state for avoiding the fatal losses of insurance companies.
Keywords: Individual insurance model; Correlated random values; Simulation; Insurance risks